2018
DOI: 10.1111/1467-9477.12117
|View full text |Cite
|
Sign up to set email alerts
|

Mediated Agency, Blame Avoidance and Institutional Responsibility: Government Communication in a Personalised Media Landscape

Abstract: This article explores how personalisation, blame avoidance and institutional constraints collide in contemporary government communication practices. Based on ethnographic fieldwork in a Norwegian ministry, it analyses how a central government agency manages the media during critical news campaigns featuring individuals suffering from inadequate public health services. To provide a comprehensive analysis of the particular limits and aims of government communication, the article combines perspectives from public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Secondly, and highly related to the first point, our comparative approach was designed to study the effects on perceived responsibility of differences in the institutional arrangements of accountability within a policy sector. We found, in accordance with previous studies (Hinterleitner and Sager 2017;Figenschou and Thorbjørnsrud 2018) that clear and transparent arrangements of accountability decreased power holders' possibilities to deflect responsibility with preserved credibility. However, through our primary focus on blame-makers instead of blame-avoiders, we also found that activists' possibilities to attribute personal blame to power holders in a credible way decreased when arrangements of accountability became complex and diffused.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Secondly, and highly related to the first point, our comparative approach was designed to study the effects on perceived responsibility of differences in the institutional arrangements of accountability within a policy sector. We found, in accordance with previous studies (Hinterleitner and Sager 2017;Figenschou and Thorbjørnsrud 2018) that clear and transparent arrangements of accountability decreased power holders' possibilities to deflect responsibility with preserved credibility. However, through our primary focus on blame-makers instead of blame-avoiders, we also found that activists' possibilities to attribute personal blame to power holders in a credible way decreased when arrangements of accountability became complex and diffused.…”
Section: Discussionsupporting
confidence: 93%
“…Despite there being a number of relevant contextual aspects influencing blame-games, the most decisive factor found in previous blame-game research seems to be the institutional context (Hinterleitner andSager 2015, 2017;Figenschou and Thorbjørnsrud 2018). Figenschou and Thorbjørnsrud studied how Norwegian Ministers responded to public blame-attributions and concluded that 'future studies should include the institutional constraints as a key condition to understanding communication in various public sector organisations ' (2018, 229).…”
Section: When Non-elites Attribute Blame-rationales Contextual Factomentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, personalized networked campaigns initiated by non-professional actors, do raise both legal and ethical dilemmas for the professional actors and institutions that are directly involved in or confronted by the personalized criticism (Figenschou & Thorbjørnsrud, 2018). For established news organizations, working with and on patients' personal stories can challenge ethical codes 2 since these narratives can test the professional balance between empathy (to listen and understand), engagement (to get involved in the story) and distance (to keep a critical overview) (Glück, 2016;Larssen & Hornmoen, 2013).…”
Section: Analytical Framework: Patient Narratives Across Mediamentioning
confidence: 99%
“…For political and medical authorities, privacy laws and principles of confidentiality in operational activities must be respected. Public authorities can neither freely comment on individual cases nor present solutions that are not anchored in due policy processes (Figenschou & Thorbjørnsrud, 2018). Professionalized interest groups and patient organizations are responsible for acting in the interest of their members -as public authorities, they must attend to privacy laws as well as prepare and brief those individuals who represent the organization in public debate (Thorbjørnsrud & Ytreberg, 2020).…”
Section: Analytical Framework: Patient Narratives Across Mediamentioning
confidence: 99%